Perkembangan Sosio-Emosional pada Pembelajaran Daring di MI Ma’arif Darussalam Plaosan Klaten - Muhamad Farizal; Maemonah Maemonah (MODELING: Jurnal Program Studi PGMI, 2021)
Social and emotional development is very important to children's intelligence in the socio-emotional aspect. The purpose of this study was to find out the development of socio-emotional intelligence in elementary school students through online learning. This research uses qualitative research type. The method used is descriptive qualitative method. By using data collection techniques in the form of unstructured interviews. In this study, it was conducted by interviewing ten parents of grade 6 students of MI Ma'arif Darussalam Klaten to get information about existing problems by using interview techniques through social media based on WhatsApp due to the current pandemic conditions. Then, analyze and study related theories. The author presents the findings of the data objectively and systematically through descriptive data analysis techniques. The subjects of this study were 10 students and families of grade 6 students at MI Ma'arif Darussalam Plaosan Klaten. The result of this study is socio-emotional intelligence is the ability that a person has to be able to recognize themselves, be able to perform social relationships, control impulses and be able to use his feelings to respond to his or her environment.